Preliminary study on the effect of nitrogen fertilization on growth quality of Gynura procumbens - Mohamad Fhaizal, Mohamad Bukhori; Hawa Z.E., Jaafar; Ali, Ghasemzadeh; Uma Rani, Sinniah (MALAYSIAN SOCIETY FOR MOLECULAR BIOLOGY & BIOTECHNOLOGY, 2021)
G. procumbens is an herbaceous medicinal plant. Despite the progressive reports on the potential pharmacological properties, many are overlooking at the importance of its agronomic requirements, especially in fertilization to produce high yields which have not been conclusively concluded. This study was carried out to examine the effects of nitrogen on growth quality. In this study of two factors, harvesting times and rate of nitrogen, a total of 12 combined treatments replicated three times with 108 plants were laid out according to randomized complete block design. Growth attributes were recorded in three harvests of triplicate samples to exhibit the trend for plant growth and quality, and statistically analysed. Nitrogen affected plant growth significantly (p≤0.05) with stronger effect on physiological attributes (p≤0.01). The results suggested that 0 nitrogen kg/ha at Week 12 and 90 nitrogen kg/ha at Week 4 is highly and least, respectively affected the morphology and physiology of G. procumbens. These attributes are controlled by the availability of usable nitrogen and agronomic management because nitrogen is needed in optimum quantity and must be in balance with other nutrients to achieve its maximum yield potential.